A Cross-Sectional Survey on the Challenges Faced by the Ayurvedic Drug Manufacturing Industry in Kerala - Saranya N; Sreeni T.V (International Journal of Ayurveda and Pharma Research, 2025)
Ayurveda is the traditional system of medicine in India. As an alternative system of medicine, it is getting global acceptance in the present decade especially in the post Covid scenario. Rising health consciousness among the people, increasing prevalence of epidemics and lifestyle diseases, evidence-based Ayurveda practices and the tremendous changes in the global trade happened in the past few years can be considered as the reason for the same. The annual turnover of Indian market of Ayurveda medicine industry in the year 1998 was 25 billion which was reached a size of INR 626 billion in the year 2022. As per the current researches it is expected to grow at a Compound Annual Growth rate of 12% from 2022 to 2028. Out of the small, medium, and large manufacturing units situated in India, 12% are situated in the state Kerala. Being a small state with such a considerable share in the market a survey has been conducted among 15 Ayurveda drug manufacturing units in the state. The paper expects to assess the possible challenges faced by the industry currently, analyze the methods to resolve them by which improve the productivity without compromising the quality of medicines. The study may also help to check the difficulties faced by the industry at the levels of collection of raw drugs, processing, manufacturing, pacing and marketing and also to suggest the necessary policy shifting if needed.